1983
DOI: 10.1021/i100012a001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate decomposition conditions in the system hydrogen sulfide-methane-propane

Abstract: We have experimentally Investigated the hydrate decomposition conditions in three different H2S-containing mixtures in the temperature region 0-30 °C. The three mixtures investigated were 4% H2S, 7% propane, 89% methane; 12% H2S, 7% propane, 81% methane; and 32% H2S, 7% propane, 61% methane. Hydrate decomposition pressures and temperatures were obtained for each of these mixtures by observation of the pressure-temperature hysteresis curves associated with formation and decomposition of the hydrate crystals. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…In perfect agreement with this reasoning, Giavarini et al (2003) verified an almost immediate formation of propane hydrate from melting ice (T op = 1 • C, P op = 4 bar) but a much slower process (13.3 t nuc (h) 18) when liquid water was employed in the reactor (T op =2 • C, P op =3.6.4.8 bar). Similar trends of an effect Table 2 Induction time for methane hydrates formed from water with different previous treatments (Vysniauskas and Bishnoi, 1983) of the thermal history of water upon the nucleation time were reported by many authors (Schroeter et al, 1983;Monfort and Nzihou, 1993;Parent and Bishnoi, 1996;Moudrakovski et al, 2001;Link et al, 2003;Lee et al, 2005a,b;Servio and Englezos, 2003;Linga et al, 2007), characterising what has been known as the memory effect in hydrate nucleation. Zatsepina et al (2004), in particular, verified that even the addition of small amounts (5-35%) of thawed water into distilled water was already enough to bring about a substantial drop in the value of t nuc .…”
Section: Experimental Studies On Hydrate Nucleationsupporting
confidence: 77%
“…In perfect agreement with this reasoning, Giavarini et al (2003) verified an almost immediate formation of propane hydrate from melting ice (T op = 1 • C, P op = 4 bar) but a much slower process (13.3 t nuc (h) 18) when liquid water was employed in the reactor (T op =2 • C, P op =3.6.4.8 bar). Similar trends of an effect Table 2 Induction time for methane hydrates formed from water with different previous treatments (Vysniauskas and Bishnoi, 1983) of the thermal history of water upon the nucleation time were reported by many authors (Schroeter et al, 1983;Monfort and Nzihou, 1993;Parent and Bishnoi, 1996;Moudrakovski et al, 2001;Link et al, 2003;Lee et al, 2005a,b;Servio and Englezos, 2003;Linga et al, 2007), characterising what has been known as the memory effect in hydrate nucleation. Zatsepina et al (2004), in particular, verified that even the addition of small amounts (5-35%) of thawed water into distilled water was already enough to bring about a substantial drop in the value of t nuc .…”
Section: Experimental Studies On Hydrate Nucleationsupporting
confidence: 77%
“…The isochoric method is the conventional technique for measuring hydrate phase equilibria based on the variation of the system pressure with temperature while keeping the volume constant [1,[15][16][17][18][19][20][21]. The hydrate phase equilibrium condition is determined by the intersection of tangents of the cooling and heating curves in the temperature and pressure trace data, which means that the hydrate equilibrium conditions highly depend on the heating curve [15][16][17][18][19][20][21].…”
Section: Isochoric Methods With Two Cycle Approach For Salt Systemsmentioning
confidence: 99%
“…The hydrate phase equilibrium condition is determined by the intersection of tangents of the cooling and heating curves in the temperature and pressure trace data, which means that the hydrate equilibrium conditions highly depend on the heating curve [15][16][17][18][19][20][21]. Several studies have given considerably focus on the accurate measurements of hydrate phase equilibria through different heating paths, such as continuous and step-wise heating methods [15][16][17][18][19][20][21]. Investigations on the hydrate phase equilibria with continuous heating were studied by several groups [15,16], while Tohidi et al [17] used a step-wise heating method and reported less scattered and more accurate data for hydrate phase equilibria.…”
Section: Isochoric Methods With Two Cycle Approach For Salt Systemsmentioning
confidence: 99%
“…During sample thawing, the last location where the frozen samples melted was in the center of the sample because of the radial heat transfer. The memory effect, in which partially organized water structures remaining from ice or dissociated hydrate promote hydrate nucleation [Schroeter et al, 1983;Sloan et al, 1998;Uchida et al, 2000b], may have been stronger in the center, since less time would have been available for this effect to decay. If this is the case, then nucleation might first occur in the center.…”
Section: 1mentioning
confidence: 99%